Promoting agricultural growth in Myanmar: A review of policies and an assessment of knowledge gaps - Tun, Than; Kennedy, Adam; Nischan, Ulrike; International Food Policy Research Institute (Michigan State University, 2015)
This paper reviews the agricultural policy environment in Myanmar up until 2014 with an eye towards identifying policies that can help to accelerate productivity and profitability in the agricultural sector. We draw heavily on the Framework for Economic and Social Reform (FESR) (2012) which provides the policy intents of the government both overall and at a sectoral level. Although limited, in some instances we rely on government data which is publicly available only up until 2010. This paper primarily examines the evolution of input policies and their measures of implementation, i.e. those focused on farm inputs (land management; finance; water management; research, education and extension services; rural electrification; seeds; fertilizer and mechanization). We also provide a brief overview of policies which affect farm diversification (including rice productivity and crop diversification) and output policies...